2005
DOI: 10.1158/0008-5472.can-04-2841
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen–Related Cell Adhesion Molecule 1a-4L Suppression of Rat Hepatocellular Carcinomas

Abstract: Carcinoembryonic antigen (CEA)-related cell adhesion molecule 1 (CEACAM1) is a member of the CEA family of immunoglobulin-like adhesion molecules with two major splice variants, CEACAM1 a -4L and CEACAM1 b -4S, differing in the length of their COOH-terminal cytoplasmic tail. Both forms are down-regulated in prostate and liver carcinomas relative to normal tissues. We have previously shown in a nude mouse xenograft model that restoration of CEACAM1 a -4L expression in human prostate carcinoma cells (PC-3) suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…Hsieh et al reported that prostatic cancer cells transfected with CEACAM1 showed reduced anchorage-independent growth and less tumorigenicity in vivo . Laurie et al reported that enforced expression of CEACAM1-4L in a rat hepatoma cell line resulted in smaller cell aggregate size in anchorage-independent growth conditions, and delayed cell-cycle progression through the G1-S phase (Laurie et al, 2005). Although these two reports seem to contradict what we observed in our study, it should be noted that the level of indigenous CEACAM1 expression was low in the cell lines they used, in contrast to HepG2 cells which have strong CEACAM1 expression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Hsieh et al reported that prostatic cancer cells transfected with CEACAM1 showed reduced anchorage-independent growth and less tumorigenicity in vivo . Laurie et al reported that enforced expression of CEACAM1-4L in a rat hepatoma cell line resulted in smaller cell aggregate size in anchorage-independent growth conditions, and delayed cell-cycle progression through the G1-S phase (Laurie et al, 2005). Although these two reports seem to contradict what we observed in our study, it should be noted that the level of indigenous CEACAM1 expression was low in the cell lines they used, in contrast to HepG2 cells which have strong CEACAM1 expression.…”
Section: Discussioncontrasting
confidence: 99%
“…CEACAM1 expression was found to be decreased in HCC compared with adjacent noncancerous regions (Tanaka et al, 1997), and the loss of CEACAM1 expression adversely affected the survival of individuals with HCC (Cruz et al, 2005). Moreover, restoration of CEACAM1 expression in rat HCC cells suppressed tumorigenesis in vivo (Laurie et al, 2005), indicating that CEACAM1 is a putative tumor suppressor in HCC. However, considering the diverse role of CEACAM1 among different types of cancer cells, it is still unclear whether CEACAM1 acts only as a tumor suppressor, including during the process of HCC metastasis.…”
Section: Introductionmentioning
confidence: 97%
“…It is therefore not surprising, that re-expression of CEACAM1-4L in rat hepatocellular carcinoma cells results in growth suppression in vitro and reduced tumour formation in vivo [48]. In contrast, expression of CEACAM1-4S in an anchorage-dependent hepatocellular carcinoma cell line promoted robust growth of the cells in soft-agar, suggesting that CEACAM1-4S-initiated signaling rendered the cells anchorage-independent [49].…”
Section: Ceacam1 Cis-oligomerization Sustained By the Transmembrane Dmentioning
confidence: 99%
“…Fluorochrome-conjugated isotype antibodies of the wrong specificity (anti Fc or mu chain specific secondary antibodies with IgM or IgG primary antibodies, respectively) were used as controls. FACS was performed as previously described (Laurie et al, 2005).…”
Section: Facs Analysismentioning
confidence: 99%